Imigração e identidade: um estudo sobre famílias portuguesas no Rio de Janeiro - Maia, Maria Manuela Alves (2008)
This is a study about immigrating Portuguese families who moved to the city of Rio de Janeiro during the period between the Second World War and 1974. The main objective is to contribute with the best visibility of the Portuguese migration to the city. Applying the methodology of their life history, this work follows the trajectory of those families since their housing in Portugal, the moving to Brazil, the arrival in the port of Rio de Janeiro and the routes traveled all along the country. Due to the shortage of agricultural resources in the North regions of Portugal, peasants families were stimulated to emigrate, aspiring better social and economic advancement, once they were inserted in a context full of multiple needs. This movement in terms of cultural or ethnic identity provokes an individual and collective transformation. As a result they went through processes of desterritorialization/territorialization, which involved ruptures in different senses. The first one took place in the dismantling of the peasants society. That is to say, within the context of the third stage of the industrial development. A second moment of the rupture is noticed during the trip and at the beginning of the staying in a foreign land. The third one can be observed through the struggles and conflicts caused by the encounter with the city. In other words, in the passage from a rural world to the urban one. In Rio de Janeiro they were forced to develop and fix up complex processes and strategies to settle. Those socio- economical strategies were configured through out cultural negotiations, where integration attempts to a new society were done based on cultural values. That negotiation is effectuated by different instruments that cover a huge panorama from a simple connection to silences and omissions. Obliged to adapt themselves to a new ways of seeing the world, the immigrants try to give a new signification to their own values. On the one hand, they consider family union as a source carrier (material, cultural and symbolic) and necessities and objectives. On the other hand, they face an attracting environment (geographical, economic, social and political) with their disadvantages and opportunities. Therefore, they emphasize the roll of family, work and religion as ways and strategies of identity affirmation in a strange land in order to guarantee family cohesion and integration to a new city